The multilayered hierarchical gene regulatory network reveals interaction of transcription factors in response to cadmium in Tamarix hispida roots. (29th December 2022) - Xie, Qingjun; Wang, Yuanyuan; Wang, Danni; Li, Jinghang; Liu, Baichao; Liu, Zhongyuan; Wang, Peilong; Zhang, Hao; Yang, Kaiye; Gao, Caiqiu
Abstract: Cadmium (Cd) is a toxic metal that affects the normal growth and development of plants. Roots may directly contact Cd and thus serve as the first barrier in the defense responses of plants. In this study, Tamarix hispida ( T. hispida ) roots treated with 150 μM CdCl2 were collected for RNA-seq. A total of 2004 differentially expressed genes (DEGs) were identified at different time points. Kyoto Encyclopedia of Genes and Genomes enrichment revealed that the DEGs were significantly enriched in phenylpropanoid biosynthesis, flavonoid biosynthesis and other metabolic pathways. To explore the regulatory role of transcription factors (TFs) involved in the Cd stress response, a multilayer hierarchical gene regulatory network (ML-hGRN) was constructed, including 53 TFs and 54 structural genes in ML-hGRN, with 341 predicted regulatory relationships. Binding of DRE1A, MYC1, FEZ, ERF4 and ERF17 to predicted target genes was detected by ChIP-PCR, and DRE1A, MYC1 and FEZ were transiently overexpressed in T. hispida. The results suggest that these TFs play a key role in the Cd stress response by scavenging reactive oxygen species. In conclusion, this study predicts some Cd-responsive TFs that may have an important function under Cd stress and provides useful information for molecular breeding.